1978
DOI: 10.1042/cs0540273
|View full text |Cite
|
Sign up to set email alerts
|

The Metabolism of Tartrate in Man and the Rat

Abstract: 1. Sodium tartrate labelled with 14 C was given orally and parenterally to man and rats, and by direct injection into the caecum in rats. From the differences in urinary excretion after oral and parenteral administration intestinal absorption of tartrate was calculated as 18% of the dose in man and 81% in rats. Urinary tartrate was equivalent to 14% of the dose in man and 70% in rats, the differ ence between absorption and urinary excretion representing metabolism in body tissues.2. Both man and the rat excret… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
30
0

Year Published

1989
1989
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(32 citation statements)
references
References 13 publications
2
30
0
Order By: Relevance
“…Based on the excretion in the urine, the results of the initial studies in humans suggested that as little as 20 % of an ingested dose of tartaric acid was absorbed from the gastrointestinal tract (Underhill et al, 1931a;Finkle, 1933). These results have been supported by Chadwick et al (1978), who demonstrated that 12 % of an oral dose of [ …”
Section: Human Datasupporting
confidence: 78%
See 1 more Smart Citation
“…Based on the excretion in the urine, the results of the initial studies in humans suggested that as little as 20 % of an ingested dose of tartaric acid was absorbed from the gastrointestinal tract (Underhill et al, 1931a;Finkle, 1933). These results have been supported by Chadwick et al (1978), who demonstrated that 12 % of an oral dose of [ …”
Section: Human Datasupporting
confidence: 78%
“…Based on the excretion in the urine, the results of the initial studies in humans suggested that 20 % of an ingested dose of tartaric acid was absorbed from the gastrointestinal tract (Underhill et al, 1931a;Finkle, 1933). These results have been further supported by Chadwick et al (1978), who demonstrated that 12 % of an oral dose of [ 14 C] tartrate was recovered unchanged in the urine of human subjects, while 46 % of the ingested radioactivity was recovered as expired CO 2 . Unabsorbed tartrate likely undergoes metabolism by the intestinal microflora, which would account for the high proportion of radioactivity recovered as exhaled CO 2 (Underhill et al, 1931a;Finkle, 1933).…”
supporting
confidence: 73%
“…This anion is partly absorbed from the digestive tract; it has been shown that colonic bacteria metabolise the bulk of ingested tartrate in human subjects, and only 14 % of ingested tartrate appears unchanged in the urine (Chadwick et al 1978).…”
Section: Absorptionmentioning
confidence: 99%
“…In the study by Chadwick et al. (), the authors confirmed that tartrate is not metabolised to oxalate, a potential metabolite with toxic properties for the kidney; most of the 14 C‐ label was recovered as 14 CO 2 . Hence, from the ADME data, it can be concluded that the metabolites would not cause potential side effects.…”
Section: Discussionmentioning
confidence: 91%
“…In the Chadwick et al. () study, rats (200–250 g) were given by gavage 20 μCi of sodium dl ‐[1,4‐ 14 C]tartrate (with 18.8 mg/kg l (+)‐tartrate as carrier). The specific radioactivity of labelled CO 2 in breath was measured every 30 minutes for 6 h and urinary excretion of [ 14 C]tartrate was measured over 24 h; faeces were not collected.…”
Section: Assessmentmentioning
confidence: 99%